SODIUM CITRATE INFLUENCE ON FORMATION OF CEMENT STONE IN THE ALUMINOUS BINDER - S. N. Leonovich; D. V. Sviridov; G. L. Shchukin; A. L. Belanovich; V. P. Savenko; S. A. Karpushenkov (Наука и техника)
The paper deals with the effect of sodium citrate on the formation of a cement stone in the aluminous binder. Formation of cement stone framework in cement hydraulic binder is accompanied with complicated physical and chemical processes of interphase interactions and dispersion, these processes are predicated on qualitative and quantitative composition of the cement mortar, continuous changes in its properties from preparation stage till curing. Addition of sodium citrate to tempering water enhances hydration of both Portland cement and calcium aluminate cement. Process pertaining to an increase of cement hydration rate is considered as a consequence of destruction in surface formations and exclusion of damping effect in respect of hydration rate and hydrolysis of products resulted from interaction of clinker material with tempering. It has been established that sodium citrate makes it possible to control processes of hydration, hydrolysis, binding and curing for cement mass. High degree of hydration of aluminous cement in the presence of sodium citrate provides fast binding and curing of binder, low porosity and rather high compression breaking strength of cement stone for all curing stages. An increase in concentration of sodium citrate in cement mixture up to 10 % of the cement mass exerts an influence not only on the process of cement mortar liquefaction, reduction of time for cement mass setting and hardening but also increases compression strength of cement stone. An analysis of the structure for cleavage surface of cement stone gives ground to declare that the addition of sodium citrate provides cement stone sealing and reduces its water absorption.